2004
DOI: 10.1152/ajpendo.00103.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced PGC-1α expression modulates muscle glucose uptake through an insulin receptor/Akt-independent, AMPK-dependent pathway

Abstract: . Cold-induced PGC-1␣ expression modulates muscle glucose uptake through an insulin receptor/Akt-independent, AMPK-dependent pathway. Am J Physiol Endocrinol Metab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
7
49
0
3
Order By: Relevance
“…The PGC-1α protein level was increased throughout cold acclimation (45 days) starting from day 3 of cold exposure. This is in accordance with previous data that showed that both short-term (4 days) and long-term (4-5 weeks) cold exposure induced PGC-1α expression in skeletal muscle (Oliveira et al, 2004;Bruton et al, 2010). PGC-1α regulates several key processes of adaptive thermogenesis in skeletal muscle, including fuel utilization and switching, insulin sensitivity, glucose transport, gluconeogenesis and lipid oxidation, mitochondrial content and function, ATP synthesis and muscle fiber differentiation Jäger et al, 2007).…”
Section: P<0001 Pgc-1α/ppars In Skeletal Muscle In the Coldsupporting
confidence: 93%
“…The PGC-1α protein level was increased throughout cold acclimation (45 days) starting from day 3 of cold exposure. This is in accordance with previous data that showed that both short-term (4 days) and long-term (4-5 weeks) cold exposure induced PGC-1α expression in skeletal muscle (Oliveira et al, 2004;Bruton et al, 2010). PGC-1α regulates several key processes of adaptive thermogenesis in skeletal muscle, including fuel utilization and switching, insulin sensitivity, glucose transport, gluconeogenesis and lipid oxidation, mitochondrial content and function, ATP synthesis and muscle fiber differentiation Jäger et al, 2007).…”
Section: P<0001 Pgc-1α/ppars In Skeletal Muscle In the Coldsupporting
confidence: 93%
“…2E). AMPK is a major regulator of skeletal muscle metabolism and has been shown to be activated to the phosphorylated form (p-AMPK) during conditions of increased energy demand including cold challenge (Koh et al, 2008;Kus et al, 2008;Oliveira et al, 2004). Upregulation of p-AMPK levels along with increased SERCA2a levels further indicate that muscle-based thermogenesis is increasingly recruited in the neonates in response to cold challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Cold and energy stress also induce the stress-activated protein kinase AMP-activated protein kinase (AMPK), which enhances EE and thus is a major target in obesity and T2D (19)(20)(21)(22)(23)(24). β-ARmediated AMPK activation augments insulin sensitivity in a UCP1-dependent manner (22).…”
Section: Introductionmentioning
confidence: 99%